Pharmacovigilance: Empowering healthcare professionals - Mugoša Snežana S.; Stanković Maja V.; Turković Nemanja M.; Bešović Željka M.; Šahman-Zaimović Majda M.; Drljević Milorad D. (Srpsko lekarsko drustvo, 2015)
Introduction: Spontaneous reporting of adverse reactions is of greatest importance for obtaining information about adverse drug reactions (ADRs) after granting the marketing authorization. The most important role and also the greatest responsibility belong to healthcare professionals. Their active participation is a prerequisite for the existence of an effective national drug safety monitoring. Methods: This paper examines the legislative framework concerning the pharmacovigilance system in Montenegro. The information was collected from scientific articles and the website of the Agency for Medicines and Medical Devices of Montenegro. Topic: Key segments of pharmacovigilance system are presented, with a special reference to the importance of spontaneous reporting of ADRs, results of spontaneous reporting of ADRs according to the latest Agency's Annual report on the results of spontaneous reporting of adverse reactions to medicines, possible reasons for underreporting ADRs, as well as the new EU regulation on pharmacovigilance. Conclusions: Spontaneous reporting of ADRs remains the cornerstone of pharmacovigilance systems. Hence, continuous education of healthcare professionals is needed, with the aim of improving their awareness of the importance of ADRs and risk factors that lead to them, in order to reduce the incidence of ADRs and to increase the number of reported suspected ADRs.